2005
DOI: 10.1081/cbi-200062397
|View full text |Cite
|
Sign up to set email alerts
|

Chronopharmacology of Morphine in Mice

Abstract: Dosing-time-dependent changes in the effect and toxicity of morphine were examined in mice housed under alternating 12 h light (07:00 to 19:00 h) and dark (19:00 to 07:00 h) cycles. Morphine (0.5 mg/kg) was injected intraperitoneally (i.p.) in animals to assess its beneficial effect (i.e., protection against the kaolin-induced, bradykinin-mediated, writhing reaction) and its toxicity (i.e., alteration of the hepatic enzymes of aspartate aminotransferase [AST] alanine aminotransferase [ALT], and glutathione [GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…1). Number of the writhing reaction was peaked at just before the active phase (dusk) and reduced during the active phase (dark period) under ad libitum feeding condition as previously reported [4,7,[18][19][20]. The number of writhes, however, was peaked from late night to morning and reduced from dusk to early night under the daytime restricted feeding condition.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…1). Number of the writhing reaction was peaked at just before the active phase (dusk) and reduced during the active phase (dark period) under ad libitum feeding condition as previously reported [4,7,[18][19][20]. The number of writhes, however, was peaked from late night to morning and reduced from dusk to early night under the daytime restricted feeding condition.…”
Section: Resultssupporting
confidence: 64%
“…In this study, we at first showed the circadian changes in the number of kaolin-induced writhing reaction in mice under a light-dark condition as previously reported [4,7,[18][19][20]. The intensity of writhing reaction is peaked at the end of the resting period (dusk) and reduced during the active (dark) period.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, nocturnally active rats as well as night shift workers were apparently little affected (Brelis, 1984). Circadian rhythmicity in host tolerance to, and toxicity of, chemical agents was first documented in laboratory experiments almost 50 yrs ago; more recent examples include ketamine/midazolam (Rebuelto et al, 2005), nedaplatin (Cui et al, 2004), irinotecan (Filipski et al, 2004), alcohol (Danel and Touitou, 2004), loratadine (Dridi et al, 2005), and morphine (Cui et al, 2005). The hypothesis of the MIC chronotoxic effect, however, has never been tested.…”
Section: Introductionmentioning
confidence: 97%
“…There are several indications that time of day influences morphine's effect in both humans and animal models [3][4][5][6][7][8][9][10][11][12][13][14]. However, the physiological mechanisms that underlie these variations in morphineinduced analgesia are unknown.…”
Section: Introductionmentioning
confidence: 99%